Moral education for women in the pastoral and Pythagorean letters: philosophers of the household - Huizenga, Annette Bourland (Supplements to Novum Testamentum, 2013)
Collection TH3: Letters of TheanoChapter Two. Female Pythagorean Teachers; Pseudepigraphy and the Pythagorean Women's Letters; The Pseudonym ""Melissa""; The Pseudonym ""Myia""; The Pseudonym ""Theano""; The Function of Female Pseudonyms in the Pythagorean Letters; Chapter Three. Teaching Strategies; The Letter Collection MM: Melissa to Kleareta and Myia to Phyllis; Rhetorical Analysis of ""Melissa to Kleareta, "" a Paraenetic Letter; Rhetorical Analysis of ""Myia to Phyllis, "" a Paraenetic Letter; The Letter Collection TH3: Theano to Euboule, Theano to Nikostrate, and Theano to Kallisto.